Cross-Linked Self-Standing Graphene Oxide Membranes: A Pathway to Scalable Applications in Separation Technologies - Juan A. G. Carrio; Vssl Prasad Talluri; Swamy T. Toolahalli; Sergio G. Echeverrigaray; Antonio H. Castro Neto (Membranes)
The large-scale implementation of 2D material-based membranes is hindered by mechanical stability and mass transport control challenges. This work describes the fabrication, characterisation, and testing of self-standing graphene oxide (GO) membranes cross-linked with oxides such as Fe2O3, Al2O3, CaSO4, Nb2O5, and a carbide, SiC. These cross-linking agents enhance the mechanical stability of the membranes and modulate their mass transport properties. The membranes were prepared by casting aqueous suspensions of GO and SiC or oxide powders onto substrates, followed by drying and detachment to yield self-standing films. This method enabled precise control over membrane thickness and the formation of laminated microstructures with interlayer spacings ranging from 0.8 to 1.2 nm. The resulting self-standing membranes, with areas between 0.002 m2 and 0.090 m2 and thicknesses from 0.6 μm to 20 μm, exhibit excellent flexibility and retain their chemical and physical integrity during prolonged testing in direct contact with ethanol/water and methanol/water mixtures in both liquid and vapour phases, with stability demonstrated over 24 h and up to three months. Gas permeation and chemical characterisation tests evidence their suitability for gas separation applications. The interactions promoted by the oxides and carbide with the functional groups of GO confer great stability and unique mass transport properties—the Nb2O5 cross-linked membranes present distinct performance characteristics—creating the potential for scalable advancements in cross-linked 2D material membranes for separation technologies.